Experiments at the interfaces - Runner, Jeffrey T., 1963- (Bingley, U.K. : Emerald, 2011)
While experimental data collection has been common in psycholinguistics for some time, only relatively recently have experimental methods been employed to collect data for research in formal linguistics. Experimental methods can be particularly useful for investigating phenomena at the interfaces of the components of grammar, where the sources of multiple types of information need to be carefully controlled. Experiments at the Interfaces, edited by Jeffrey T. Runner from the University of Rochester, brings together recent experimental research examining a variety of issues within syntax and semantics, and their interfaces with each other and with other domains of language. The volume showcases a wide range of experimental methods and illustrates how they can be applied to critical questions relevant to formal linguistics.
1. Interface effects : Serbian clitics / Molly Diesing, Draga Zec -- 2. I'm leaking oil and looking for a garage / Sam Featherston, Klaus von Heusinger, Hanna Weiland -- 3. Tracking the preference for bound-variable dependencies in ambiguous ellipses and only / Arnout W. Koornneef, Sergey Avrutin, Frank Wijnen, Eric Reuland -- 4. Most meanings are superlative / Hadas Kotek, Yasutada Sudo, Edwin Howard, Martin Hackl -- 5. Grammatical illusions and selective fallibility in real-time language comprehension / Colin Phillips, Matthew W. Wagers, Ellen F. Lau -- 6. Seeing what you mean, mostly / Paul Pietroski, Jeff Lidz, Tim Hunter, Darko Odic, Justin Halberda -- 7. On the representational nature of representational noun phrases / Jeffrey T. Runner, Micah B. Goldwater.
Includes index.
Keywords: Language Arts & Disciplines -- Linguistics -- Semantics; Language Arts & Disciplines -- General; Semantics; Linguistics